Asset Maintenance Monitoring Application: A Case Study of a Government Bank Branch Office - Anggraini, Julaiha Probo (Journal of Computer Science Advancements, 2023)
Asset management in a company is essential to do. Asset management may include record keeping, maintenance, and management environment further. Recording information asset owned by a company is the primary and most important thing to do to record data assets owned by the company. The existence of definite information about the asset owned by a company will provide convenience for the company that is and automatically, the company will also easier to carry out the asset management process further. One of the governments in the Jakarta Branch, which has assets, should be maintained. Recording information assets in one of the government banks, Jakarta Branch, is only partially managed with a computerized system. The process of recording data assets is still done manually and also not maximum. This research developed an Asset Monitoring Application Maintenance feature that can do registration detail information about the attributes and Monitoring of existing assets and Online Work Order. The software development model used in this study is the waterfall model. This thesis will explain the activities in each development phase. With this application, all the attributes of data assets owned by the company can be well identified and inventoried so that the process of monitoring assets is more optimum and easier to do